Using K-Means Clustering to Enhance Digital Marketing with Flight Ticket Search Patterns - Husni Teja Sukmana; Lee Kyung Oh (Journal of Digital Market and Digital Currency, 2024)
This study explores the application of K-Means clustering to enhance digital marketing strategies by analyzing flight ticket search patterns. Utilizing a dataset containing 4,000 search engine results related to flights to Hong Kong, the research identifies five distinct user clusters based on search terms, titles, snippets, and other relevant features. The dataset's key features include search terms, ranks, titles, snippets, display links, and direct links, providing a comprehensive view of user interactions and preferences. The cluster analysis reveals significant variations in user intent and preferences across the identified segments. For instance, Cluster 1 is characterized by users searching for "cheap flights" and "discount tickets," indicating a price-sensitive segment. In contrast, Cluster 2 users prefer "premium flights" and "business class," highlighting an interest in luxury travel options. The study also examines the behavioral patterns within each cluster, such as Cluster 3 users who search for flights well in advance and prioritize flexible booking options. The findings underscore the effectiveness of K-Means clustering in enhancing digital marketing strategies. By leveraging the insights from the clustering analysis, marketers can design highly targeted advertising campaigns and personalized offers. For example, budget airlines can target Cluster 1 with promotions and discounts, while premium airlines can focus on Cluster 2 with exclusive service highlights. This targeted approach is expected to improve user engagement and conversion rates significantly. The study also highlights the advantages of behavior-based segmentation over traditional demographic methods, offering a more accurate representation of user preferences and intentions. The identified clusters provide a framework for understanding different user groups, enabling more efficient resource allocation and campaign design. Future research should explore the integration of additional data sources, such as social media interactions and user reviews, to enhance clustering accuracy. Additionally, advanced clustering techniques like hierarchical clustering and Gaussian Mixture Models could be investigated to provide further insights. The ongoing refinement and enhancement of segmentation processes are crucial for maintaining effective and impactful digital marketing strategies in the dynamic travel industry. Key results include the identification of five user clusters, the importance of personalized marketing strategies, and the potential for improved engagement and conversion rates through targeted advertising and offers.